Basic Violet Decolourization Using Alginate Immobilized Nanozirconium Tungestovanadate Matrix as Cation Exchanger. (13th September 2015) - Elkady, M. F.; Shokry Hassan, H.; El-Sayed, Eman M.
Abstract : As an innovative cation exchange material, nanozirconium tungestovanadate prepared using homogeneous precipitation technique was immobilized into alginate matrix and evaluated for cationic dye decolourization. Physicochemical properties of the prepared composite material were examined to determine its crystallinity, morphology, and ion exchange capacity. The SEM and TEM images of the prepared zirconium tungestovanadate identified that it was prepared in homogeneous structure with spherical shape in average diameter 22 nm. However, the optical microscope image of the composite matrix confirms the good distribution of nanozirconium tungestovanadate into the polymeric matrix. Batch technique was utilized to test the cation exchange efficiency of the prepared composite material toward C.I. basic violet 16 dye decolourization. The optimum immobilized dosage from nanozirconium tungestovanadate into the polymeric matrix to achieve 99% dye decolourization from 50 ppm initial dye concentration was recorded as 8 g/L. The dye sorption process onto the prepared material is described as an endothermic process. The dye sorption process at equilibrium was following both Langmuir and Freundlich isotherm models. The kinetic sorption behaviour of dye onto the composite matrix is correlated to pseudo-second-order equation model.